A review of Momordica species in Africa (Cucurbitaceae): current knowledge and perspectives for sustainable managemen - Assogbadjo, Cossi Sosthène; Avocèvou-Ayisso, Carolle; Idohou , Rodrigue; Wouyou, Hyacinthe Gbètoyénonmon; Houndonougbo , Juliano Sènanmi Herman; Hounsou-Dindin , Guillaume; Assogbadjo , Achille Ephrem (Ethnobotany Research and Applications, 2025)
Background: African Indigenous Vegetables (AIVs), particularly species of the genus Momordica, are crucial for West African communities, offering nutritious leaves, fruits, and seeds used both as food and traditional medicine. Earlier publications emphasized the significance of the genus Momordica, focusing on pharmacology, traditional uses, and biochemical components. However, current knowledge and research on sustainable management policies remain limited. This study presents a comprehensive systematic review of the past three decades, highlighting publication trends and key insights on the conservation ecology and domestication of Momordica species in Africa. Methods: The search was conducted in four academic databases and covered peer-reviewed literature from 1993 to 2023. This systematic review initially identified 1,480 potentially relevant publications. Through a sequential screening process, beginning with evaluating titles, keywords, and abstracts, followed by a full-text assessment based on predefined inclusion criteria, 128 studies (8.6%) were ultimately selected for in-depth analysis. Results: A systematic analysis of the literature reveals that research on Momordica species has been geographically uneven across Africa. The majority of studies have been concentrated in West Africa (n = 89). Momordica charantia L. (n = 59), Momordica balsamina L. (n = 20), and Momordica. foetida Schumach. (n = 18) emerged as the most frequently investigated species. Despite growing interest, the systematic review reveals significant research gaps, especially regarding ecosystem services, genetic diversity, and the conservation status of Momordica species across Africa. Conclusion: Addressing these gaps could facilitate more informed decision-making and promote sustainable strategies for the ongoing domestication of these species in Africa. Keywords: African Indigenous Vegetables, genus Momordica, Ethnobotany, Conservation biology, Domestication.